Aplikasi Akad Murabahah Pada Pembiayaan BSM Oto Di Bank Syariah Mandiri KCP Ponorogo - Kadenun, Kadenun Kadenun; Yuliana, Lidya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Murabahah contracts are one of the most dominant financing contracts used by banking practitioners. The ideal in murabahah transactions in banking is to require buying and selling transactions between the bank and the owner of the goods (supplier), and between the bank and the customer. However, in practice what occurs is a sale and purchase transaction between the supplier and the customer as evidenced by the BPKB or cover note issued by the goods provider. Here it is as if the bank only acts as a provider of funds for customers and its position is not as a buyer, but solely as a user of financing services provided by the bank. Based on the problems mentioned above, the author wants to examine in more depth the murabahah contract for Bank Syari'ah Mandiri financing to make it clearer. The objectives of this research are: (1) To determine the application of murabahah in BSM OTO financing at Bank Syariah Mandiri KCP Ponorogo ? (2) To find out the factors that become obstacles in implementing the murabahah contract for BSM OTO financing at Bank Syariah Mandiri KCP Ponorogo ? Meanwhile, the method used in this research is a qualitative descriptive method. Data collection techniques in this research are through observation, interviews and observation techniques. The location for this research is Bank Syari'ah Mandiri (BSM) OTO KCP ​​Ponorogo (which has now changed its name to Bank Syari'ah Indonesia/BSI KCP Ponorogo). Based on data analysis, it was concluded that: (1) The application of the murabahah contract for financing BSM OTO KCP ​​Ponorogo uses the murabahah bi al-wakalah contract. (2) Meanwhile, the obstacles to the application of murabahah contracts for BSM OTO financing are: Banks are unable to fulfill several provisions in the DSN fatwa, recipients of car ownership financing are late in paying installments beyond the specified time limit, recipients of car ownership financing are unable to pay the installment amount, such as which has been agreed due to bankruptcy, the risk of movable collateral has a high risk because if execution occurs the goods could move to another place further from the customer's residence, and in terms of marketing the bank will be less competitive with leasing companies.